Intensity modulated radiotherapy (IMRT) or conformational radiotherapy (3D-CRT) with conventional fractionation for prostate cancer: Is there any clinical difference? - Viani,Gustavo (2019)
ABSTRACT Purpose: To compare the treatment outcomes of a cohort of prostate cancer patients treated with conventional schedule using IMRT or 3DRT technique. Materials and Methods: Between 2010-2017, 485 men with localized prostate cancer were treated with conventional radiotherapy schedule with a total dose ≥74Gy using IMRT (231) or 3DCRT (254). Late gastrointestinal (GI) and genitourinary (GU) toxicity were retrospectively evaluated according to modified RTOG criteria. The biochemical control was defined by the Phoenix criteria (nadir + 2ng/mL). The comparison between the groups included biochemical recurrence free survival (bRFS), overall survival (OS) and late toxicity. Results: With a median follow-up of 51 months (IMRT=49 and 3DRT=51 months), the maximal late GU for >=grade- 2 during the entire period of follow-up was 13.1% in the IMRT and 15.4% in the 3DRT (p=0.85). The maximal late GI ≥ grade- 2 in the IMRT was 10% and in the 3DRT 24% (p=0.0001). The 5-year bRFS for all risk groups with IMRT and 3D-CRT was 87.5% vs. 87.2% (p=0.415). Considering the risk-groups no significant difference for low-, intermediate- and high-risk groups between IMRT (low-95.3%, intermediate-86.2% and high-73%) and 3D-CRT (low-96.4%, intermediate-88.2% and high-76.6%, p=0.448) was observed. No significant differences for OS and DMFS were observed comparing treatment groups. Conclusion: IMRT reduces significantly the risk of late GI severe complication compared with 3D-CRT using conventional fractionation with a total dose ≥74Gy without any differences for bRFS and OS.